Masterpieces Of Applied Art Of The Museum “Iсhan Qal’a” - Sultanova Gulchekhra Ozodovna (Zien Journals, 2021)
This article provides information about the establishment of the Khiva State Museum-Reserve “Ichan Qal’a” and its collections of applied arts, Khorezm masters of applied arts, unique exhibits in the museum.
Keywords: Khiva; column; door; excursion